Halogen bonding-enhanced electrochemical halide anion sensing by redox-active ferrocene receptors1. Issue 78 (7th October 2015) - Lim, Jason Y. C.; Cunningham, Matthew J.; Davis, Jason J.; Beer, Paul D.
<x xml:space="preserve">Abstract</x> The first redox-active halogen bonding anion receptors display larger electrochemical voltammetric responses to halide binding compared to their hydrogen bonding analogues.